The wall as an urban liminality: on fictional Manhattan and Cambridge - Rosmaninho, João (2020)
Walls imply war and vice-versa. Walls, for instance, are often highlighted as urban elements that both separate and capture. Although their consequences have several forms yet to analyze, one may find in recent literary dystopias a very precise and realistic representation of them. In fact, walls reveal with accuracy violent architectures that characterize part of our human and urban cultures. Hence, it comes as no surprise that narratives such as “In the Country of Last Things” or “The Handmaid’s Tale” can definitely represent liminal places (and regimes) at war with walls amongst them. Following this outcome, our communication seeks to address how these specific elements have become a display for fictional visions adapting, depicting, and assembling versions of the urban space. Through two fictional settings located in the near future (as it happens in Paul Auster’s and Margaret Atwood’s novels), we aim to investigate urban liminalities produced by walls as relevant ones to define our present condition and its built environment. According to these authors, we may enhance multiple understandings of reality and scrutinize our collective existence using the conventions of fiction.